Dissecting the phenotypic and genetic spectrum of early childhood-onset generalized epilepsies. (October 2019) - Kim, Soo Yeon; Jang, Se Song; Kim, Jong-Il; Kim, Hunmin; Hwang, Hee; Choi, Ji Eun; Chae, Jong-Hee; Kim, Ki Joong; Lim, Byung Chan
Highlights: Early childhood-onset generalized epilepsies have an overlapping genetic and phenotypic spectrum. Two-thirds of the pathogenic variants were found in SLC6A1, SLC2A1, and SYNGAP1. SLC6A1 mutation is responsible for 15% (3 out of 20) of early onset absence epilepsy. Abstract: Purpose: Although the genetic and clinical aspects of epilepsy with myoclonic-atonic seizures (MAE) and early onset absence epilepsy (EOAE) have been investigated thoroughly, other early childhood-onset generalized epilepsies that share clinical features with MAE and EOAE have not been characterized. In this study, we aimed to delineate the genetic and phenotypic spectrum of early childhood-onset generalized epilepsies, including MAE and EOAE. Methods: We recruited 61 patients diagnosed with MAE, EOAE, genetic epilepsy with febrile seizure plus (GEFS+) and unclassified generalized epilepsies that shared seizure onset age and seizure types. Genetic causes were investigated through targeted gene panel testing, whole exome sequencing, chromosomal microarray, and single-gene Sanger sequencing. Results: We classified 11 patients with MAE, 20 with EOAE, 9 with GEFS + spectrum. Epilepsy syndrome was not specified in the remaining 21 patients. The clinical features were comparable across groups. Nevertheless, patients with EOAE tended to show better developmental and seizure outcomes. A total of 23 pathogenic sequences and copy number variants from 12 genes were identified (23/61, 37.7%). Genetic etiologies were confirmed in 36.4% (4/11) of the MAE group, 45% (9/20) of the EOAE group, 22.2% (2/9) of the GEFS + spectrum, and 38.1% (8/21) of the unclassified group. The most frequently identified genes with pathogenic variants were SLC6A1 (7 patients), SLC2A1 (4 patients), and SYNGAP1 (4 patients). Conclusion: Early childhood-onset generalized epilepsy appeared to be characterized by an overlapping genetic and phenotypic spectrum. SLC6A1 and SLC2A1 appeared to be important genetic causes of early childhood-onset generalized epilepsy.